Effects of zeolite supplementation on parameters of intestinal barrier integrity, inflammation, redoxbiology and performance in aerobically trained subjects - Lamprecht, M.; Bogner, S.; Steinbauer, K.; Schuetz, B.; Greilberger, J.; Leber, B.; Wagner, B.; Zinser, E.; Petek, T.; Wallner-Liebmann, S.; Oberwinkler, T.; Bachl, N.; et al. (Journal of the International Society of Sports Nutrition, 2015)
Zeolites are crystalline compounds with microporous structures of Si-tetrahedrons. In the gut, these silicates could act as adsorbents, ion-exchangers, catalysts, detergents or anti-diarrheic agents. This study evaluated whether zeolite supplementation affects biomarkers of intestinal wall permeability and parameters of oxidation and inflammation in aerobically trained individuals, and whether it could improve their performance.